Inversion method of the key structure parameters of light screen array measurement system using genetic algorithm - Chen, Rui; Chen, Ding; Ji, Bowen; Ni, Jinping (Optik (Stuttgart), 2020)
To effectively improve the measurement accuracy of the light screen array measurement system (LSA for short) in the evaluation of continuous rapid-firing weapon, the paper presents an inversion method to obtain the key structure parameters of LSA based on genetic algorithm. First, we systematically introduce a measurement model based on the key structure parameters of the LSA. Second, we establish an objective function through the validation of the measurement results. Next, an inversion method is derived to generate many groups of structural parameters within the allowable error range. Finally, we can adopt a genetic algorithm to obtain a group of the key structural parameters which are the closest to their truth value. Through simulations and experiments, results show that the measurement model is corrected because of the key structural parameters through the inversion, and thus the accuracy of the LSA is effectively improved.